Fabrication and cytotoxicity assessment of novel polysiloxane/bioactive glass films for biomedical applications. Issue 14 (1st November 2016) - Francis, A.; Detsch, R.; Boccaccini, A.R.
Abstract: This work evaluates for the first time the cyto-compatibility of silicone (polysiloxane)/bioactive glass composite films produced by dip coating on stainless steel substrates using osteoblast-like (MG-63) cells. With the aim of creating corrosion resistant coatings for biomedical applications, bioactive glass (BG) of 45S5 composition was used as a filler in conjunction with commercial silicones (MK and H62C). Bioactive glass has the property of forming a direct bond to living bone, and polysiloxane is an attractive candidate for protective coatings due to its resistance to oxidation and corrosion. Suspensions based on polysiloxanes (MK/H62C) and micro-sized BG fillers were used for dip coating stainless steel substrates at room temperature, followed by curing in oxidative atmosphere at 260 °C and 500 °C. Fourier transform infrared spectroscopy (FTIR) analysis revealed the presence of Si–O–Si, Si–OR, Si–CH3 and Si–OH groups on the substrate. Field emission scanning electron microscopy showed that the coatings were homogeneous with no obvious cracks or pinholes at relatively high concentrations of both polysiloxane and BG. The cell biology experiments confirmed that the expressed cell-morphology, analyzed on chosen surfaces, was pheno-typical for MG-63 cells after 48 h of incubation. On the film containing the lower amount of polysiloxane/BG the most dense cell layer was formed. Our results indicated that polysiloxane/BG composite films exhibited good cyto-compatibility at 260 °C and 500 °C and showed no toxicity toward MG-63 cells suggesting the potential of this composite for applications in medical implants.